Elevated CO2 Atmosphere Minimizes the Effect of Drought on the Cerrado Species Chrysolaena obovata - Oliveira, Vanessa F.; Silva, Emerson A.; Carvalho, Maria A. M. (Frontiers in Plant Science, 2016)
Chrysolaena obovata stores inulin in the rhizophores, associated with drought tolerance. While crop plants are widely studied concerning the interactive effects of high [CO2] and drought, few studies reported these effects in native species. Here we evaluated the combined effects of these factors on water status and fructan metabolism in C. obovata, a native Cerrado species. Two lots of plants were kept at 380 and 760ppm [CO2] in open-top chambers. In each [CO2] plants were divided in four groups and cultivated under different water availability: irrigation with 100 (Control), 75 (low), 50 (medium) and 25% (severe drought) of the water evapotranspirated in the last 48 h. In each water treatment plants were collected at 0, 9, 18 and 27 d. On day 27, all plants were re-watered to field capacity and, after 5 days, a new sampling was made. Water restriction caused a decrease in plant moisture, photosynthesis and in enzymes of fructan metabolism. These changes were generally more pronounced in 25% plants under ambient [CO2]. In the later, increases in the proportion of hexoses and consequent modification of the fructan chain sizes, were more marked than under high [CO2]. The results indicate that under elevated [CO2], the negative effects of water restriction on physiological processes were minimized, including the maintenance of rhizophore water potential, increase in water use efficiency, maintenance of photosynthesis and fructan reserves for a longer period, conditions that shall favor the conservation of this species in the predicted climate change scenarios.